How to harnesses digital technologies for pursuing business model innovation: a longitudinal study in creative industries - Priyono, A. (Emerald Group Holdings Ltd., 2021)
Purpose: This study aims to investigate how manufacturing firms in the creative industries harness digital technologies to undertake business model innovation. Design/methodology/approach: This study used in-depth case studies to examine the complex interplay between digital technologies and business model innovation. A longitudinal approach was selected to capture major events both within the firm and in the business environment. Building on the firmâs archival data, interviews and secondary data that was available to the public, the authors carefully analyzed impactful digital technology events and the firmâs responses to the technological changes that occurred over the period of 2004â2020. Findings: The findings suggest that digital technologies alone are not sufficient for business model innovation to be successful; support from sociotechnical factors is also required. Additionally, firms should reinvent a new business model when the existing ones seem to start to diminish. Research limitations/implications: In this study one firm was examined as the subject, using a qualitative method. This method allowed us to observe complex interplays among the resources required in business models. Future research can combine qualitative methods with computational case studies, which utilize a large volume of quantitative big data. Practical implications: The results of this study suggest that managers must ensure that the resources within and outside organizations are loosely connected and are readily available to be mobilized for supporting business model innovation. To enable this, managers must prepare the required resources in advance. Originality/value: The current findings add to a growing body of literature on business model innovation and digital technologies. In particular, this study describes the process of how a traditional firm from a least developed country pursues business model innovation with the support of digital technologies. Â© 2021, Emerald Publishing Limited.